Semi-analytical and numerical estimates of anchor losses in bistable MEMS. (15th August 2016) - Frangi, A.; Cremonesi, M.
Abstract: Anchor losses are one of the dominant sources of dissipation in micro-structures and their influence is even increased in the presence of axial loads. MEMS in which they are likely to play a major role include bistable elements which are nowadays commonly employed in shock sensors and energy harvesters. In this contribution we compute anchor losses both with a semi-analytical approach based on the theory of beams and a fully 3D finite element method including PML for wave dissipation. The two techniques provide coherent predictions and confirm the expectations of strong anchor losses. A fully analytical model is also proposed in the range of limited compressive forces and represents a valid tool for the design of new devices.